Developing a Holistic Framework for Teaching Effectiveness: An Analytical Study on Multiple Dimensions and Stakeholder Perspectives (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Online learning management systems have become well-known resources for students all across the globe. Since the COVID-19 pandemic abruptly shifted conventional education online, there has been a prenominal growth in the number of e-learning systems providing diverse services, reflecting the clear relevance of e-learning in higher education. Therefore, evaluating e-learning platforms is crucial for their efficient use and smooth rollout. With the help of the relevant literature, we were able to construct a comprehensive model that combines the ISSM and TAM to show how various aspects of e-learning systems affect their performance. Using empirical data collected from a survey questionnaire of 537 students from three private institutions in India, the suggested model is used to evaluate theory-based hypotheses using structural equation modeling.